Teaching in Grief: Critical Reflections, Redefining Justice, and a Reorientation to Teaching - Moore, Heather Cherie (Radical Teacher, 2016)
Since the creation of the #BlackLivesMatter movement, many scholars from historically underrepresented communities have revisited discourse on social movements. Many supporters of the #BlackLivesMatter movement are outsiders participating in solidarity with organizers across the globe. But what happens when questions of police brutality and injustice adversely impact your family and your career? Using the self-narrative method and grief framework, the author describes her teaching transformation in a pilot Multicultural Education course immediately following the death of her cousin in police custody. The author describes how the terms injustice, action, and pedagogy changed over time and took on new meanings during an extended grieving period.